Accurate Tunable‐Gain 1/x Circuit Using Capacitor Charging Scheme. Issue 5 (1st October 2015) - Yang, Byung‐Do; Heo, Seo Weon
Abstract : This paper proposes an accurate tunable‐gain 1/ x circuit. The output voltage of the 1/ x circuit is generated by using a capacitor charging time that is inversely proportional to the input voltage. The output voltage is independent of the process parameters, because the output voltage depends on the ratios of the capacitors, resistors, and current mirrors. The voltage gain of the 1/ x circuit is tuned by a 10‐bit digital code. The 1/ x circuit was fabricated using a 0.18 μm CMOS process. Its core area is 0.011   mm 2 ( 144 μ m × 78 μ m ), and it consumes 278 μW at V DD = 1.8 V and f CLK = 1 MHz . Its error is within 1.7% at V IN = 0.05 V to 1 V.